Service Quality in Engineering Graduate Programs Using SERVQUAL-TRAN - พริบไหว, ศักดิ์ระพี; คุปตัษเฐียร, ณฐา (Frontiers in Engineering Innovation Research, 2015)
The objective of this research was to study the satisfactions of graduate study service at the department of Industrial Engineering, faculty of Engineering, Rajamangala University of Technology Thanyaburi. This study compared to the differences between the expectations and satisfactions with in the service quality of service received by students using SERVQUAL-TRAN technique. The researchers studied a sample of 99 graduate students. The results found that lower levels of satisfaction, when the comparing service expectation with satisfaction. The key issues that must be improved as 1) staff response, 2) adequate student services, 3) student feedback, 4) student records management system, and 5) life-long learning. However when used t-test to test the difference between the average of expectations on service quality and satisfaction of service learning, the students satisfied with 1) Students possess ethics, 2) Ability to implement knowledge, 3) Students have related personaliy skills and responsibility, 4) Detailed course materials are provided by teaching faculty, 5) Teaching faculty give prompt responses to students’ requests, 6) Students receive prompt, individual attention from teaching faculty.